Effect of COVID-19 on dental telemedicine in Japan - Masaki Morishita; Osamu Takahashi; Shinji Yoshii; Masanari Hayashi; Ryota Kibune; Taiji Nakamura; Kosuke Muraoka; Kazuhiro Tominaga; Shuji Awano (Elsevier, 2022)
Background/purpose: In Japan, medical and dental care is provided by the universal health insurance system. The Ministry of Health, Labour, and Welfare (MHLW) in Japan sets the rules for health care services provided by health insurance. The MHLW issued a notice in 2020 permitting telemedicine and dental telemedicine for the first visit and for follow-up visits to prevent the spread of COVID-19 infection. We conducted this study to clarify the status of dental telemedicine during 2020. Materials and methods: We used data from lists obtained on the MHLW website in the analysis. We investigated the number of dental institutions conducing dental telemedicine for the first visit and for follow-up visits by prefecture. Results: In each prefecture, fewer dental institutions conducted telemedicine for the first visit than for follow-up visits. Regions with large metropolitan areas had higher numbers of dental institutions conducting dental telemedicine for the first visit and follow-up visits. Private dental clinics provided the largest proportion of dental telemedicine for the first visit, and general hospitals provided the largest proportion for follow-up visits. Conclusion: Our study findings indicated that many dental institutions in Japan made efforts to provide dental services via dental telemedicine using the telephone or online with video to help prevent the spread of COVID-19 infection. Dental telemedicine can help patients to access dental services and dental care, thereby expanding the potential of dental telemedicine in Japan.